STRATEGI PEMASARAN UMKM COFFEE SHOP BERTAHAN DALAM MASA KRISIS KEUANGAN DI ERA PANDEMI COVID-19 (Studi Kasus Pada UMKM Kedai Kopi ?Webe? di Bojong Nangka Kabupaten Tangerang) - Amali, Muhazimatul; Kusumadewi, Shynthia; Resi, Resi; Aulia, Ramadanti; Septiani Mahira, Navila (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2025)
The COVID-19 epidemic has caused considerable disruptions in a number of spheres of life, including the corporate world. Social restrictions and lockdowns imposed in various countries have paralyzed economic activity, disrupted supply chains, and triggered a business crisis on a global scale. The COVID-19 control policy, which interfered with MSME operations, was the cause of this. As a result, many MSMEs have decreased income, even no income. MSMEs must overcome these conditions in order to survive. The purpose of this study is to use qualitative approaches to ascertain the Wedang Bubuk coffee shop's survival strategy amid the Covid-19 pandemic crisis.